An Assessment of the Performance of the Japanese Health Care System - Jeong, Hyoung-Sun (OECD Publishing, 2001)
There is much interest in the Japanese health care system from the perspective of other OECD countries. The Japanese health care system appears to perform well. What explains this apparently good performance? This paper aims both to provide a description of how the Japanese health system works and an assessment of its performance in the context of an international comparison. The Japanese health care system is characterised by public health insurance with mainly private providers. Japan has universal public health insurance with coverage of a comprehensive range of services and only modest cost sharing by patients. It has mainly private providers paid mainly by fee-for-service. The share of its population that is elderly is above the OECD average. Such a combination would usually be associated with high levels of health expenditure. Yet less is spent on health care in Japan than would be expected for an OECD country with its standard of living. Cost containment seems to have been ...
Keywords: Social Issues/Migration/Health; Japan